Engineering multi-agent systems : 5th international workshop, EMAS 2017, Sao Paulo, Brazil, May 8-9, 2017, revised selected papers /: 5th international workshop, EMAS 2017, Sao Paulo, Brazil, May 8-9, 2017, revised selected papers. (2018) - Unknown
No abstract available